Qualidade do mamão Formosa: efeitos do pré-resfriamento, atmosfera modificada e ácido peracético - Miguel, Luiza celeste Vieira (2021)
Papaya has a climacteric type of breathing pattern, it is considered a very perishable fruit, requiring the use of post-harvest technologies to delay senescence, maintain its quality and its post-harvest conservation potential. Thus, the objective of this study was to evaluate the use of post-harvest technologies to maintain quality and increase the useful life of papaya Formosa intended for export. For this, two experiments were carried out: in the first experiment, the effect of pre-cooling on the quality and conservation of Formosa 'Tainung I' papaya harvested in the ripening stage II, conducted in a completely randomized design (DIC), was evaluated in a scheme of 4 x 6 subdivided plots, with plots consisting of the pre-cooling treatments [I - control fruits (without pre-cooling), II - pre-cooling to 15 ° C in a cold chamber (15 ° C-CF), III - pre-cooling to 7 ° C in a cold chamber (7 ° C-CF) and IV - pre-cooling to 7 ° C in a forced air chamber (7 ° C-AF)] and the subplots for the evaluation periods during the storage (0, 7, 14, 21, 28 and 35 days), with four repetitions of two fruits each. In the second experiment, the effect of using the modified atmosphere and peracetic acid on postharvest conservation of organic Formosa 'Tainung I' papaya was evaluated, conducted in DIC in a split plot scheme with two factors in the plot and one in the subplot (2 x 3 x 5), with the parcels constituted by the peracetic acid treatments (with and without acid - 500ppm) and the types of packaging (Xtend® 815-pp64, Xtend® 815-pp65 and without packaging), and the subplots constituted by the periods of evaluation during storage (0, 10, 18, 26, 34 days), with five repetitions, each of them having a fruit. For the first experiment, it was concluded that the pre-cooling delayed the ripening and senescence of papaya Formosa, reducing the loss of green color and firmness. The appearance of cold damage and the incidence of fungi of the genus Fusarium and Alternaria limited the useful life of the beautiful papaya ‘Tainung I’ in this study, regardless of treatment, up to 21 days of storage. The appearance of hardened regions in the pulp of the fruit, compromised its sensorial quality of the fruits, deserving a deeper investigation about the causes of this disorder. For the second experiment, the treatment with peracetic acid associated with the use of packaging during storage maintains the postharvest quality of the organic papaya Formosa ‘Tainung I’. The association of peracetic acid and the use of packaging 1 (Xtend® 815 pp64) provided maintenance of the levels of vitamin C, soluble solids, sugar content and beta-carotene. The peracetic acid associated with packaging 2 (Xtend® 815 pp65) provided a better external appearance of the organic Formosa ‘Tainung I’ papaya, with an acceptable commercial standard for up to 26 days